The Relationship between Emotional Maturity and Self-Efficacy With Career Maturity in Class XI Students of SMAN 1 Jakarta - Maharini Oktavia, Devega; Kurniawan, Dicky (International Journal of Social Science, Education, Communication and Economics, 2024)
This research is a quantitative study which aims to examine the relationship between emotional maturity and self-efficacy and career maturity in class XI students at SMAN 1 Jakarta. The research population was 290 students of class The instrument of this research uses 3 scales, namely the Career Maturity scale, emotional maturity and self-efficacy with bivariate and multivariate correlation analysis techniques processed using SPSS 15.0 For Windows. The results of bivariate correlation data analysis on emotional maturity and career maturity obtained r = 0.301, p = 0.000 where p < 0.01. So (Ha1) which reads "There is a relationship between emotional maturity and career maturity in class XI students at SMAN 1 Jakarta" is accepted." The results of bivariate correlation data analysis on self-efficacy and career maturity obtained r = 0.242, p = 0.002 where p < 0.01. So (Ha2) which reads "There is a relationship between self-efficacy and career maturity in class XI students at SMAN 1 Jakarta" is accepted." The multivariate correlation coefficient of emotional maturity and self-efficacy with career maturity in class So Ha3) which states "there is a relationship between emotional maturity and self-efficacy and career maturity in class students at SMAN 1 Jakarta" is accepted.